Effects of Enteromyxum scophthalmi experimental infection on the neuroendocrine system of turbot, Scophthalmus maximus (L.) - A. P. Losada; R. Bermúdez; L. D. Faílde; M. I. Quiroga; A. Di Giancamillo; C. Domeneghini (Fish & Shellfish Immunology, 2014)
Enteromyxum scophthalmi is an intestinal myxosporean parasite responsible for serious outbreaks in turbot Scophthalmus maximus (L.) culture, in North-western Spain. The disease affects the digestive tract, provokes severe catarrhal enteritis, emaciation and high rates of mortality. The digestive parasitization triggers a response with the coordinate participation of immune and neuroendocrine systems through the action of peptides released by enteroendocrine cells and present in nervous elements, acting as neuro-immune modulators. The present study was designed to assess the response of the turbot neuroendocrine system against E.scophthalmi infection. Immunohistochemical tests were applied to sections of the gastrointestinal tract of uninfected and E.scophthalmi-infected turbot to characterize the presence of bombesin (BOM), glucagon (GLUC), somatostatin (SOM), leu-enkephalin (LEU) and met-enkephalin (MET). The occurrence of E.scophthalmi in the turbot gastrointestinal tract increased the number of enteroendocrine cells immunoreactive to SOM, LEU and MET. On the other hand, BOM and GLUC immunoreactive cells were less numerous in the gastrointestinal tract of the parasitized turbot. Scarce immunoreactivity to BOM, GLUC and SOM was observed in nerve fibres and neurons of the myenteric plexus of control and infected fish. The results indicate that E.scophthalmi infection in turbot induced changes in the neuroendocrine system, with the diminution of the anorexigenic peptides BOM and GLUC; the increase of enkephalins, related to pro-inflammatory processes; and the increase of SOM, which may cause inhibitory effects on the immune response, constituting a compensatory mechanism to the exacerbated response observed in E.scophthalmi-infected turbot.